Ethnic stereotypes in Polish and Czech proverbs - Raina, Olga V.; Shestakova - Stuk, Alena S. (Bohemistyka, 2019)
Proverb is a genre of folklore and it is thought reflection of the whole nation. The proverbs contain rich material about the perception of the world and reflect the specific conditions of development of material and spiritual culture. The examined proverbs illustrate the stereotypes of the Poles and Czechs about themselves, their neighbours and other nations.